The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/foods10112811
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Beef Patties Substituted by Different Levels of Textured Vegetable Protein and Taste Traits Assessed by Electronic Tongue System

Abstract: The main objective of this study was to incorporate soy-based textured vegetable protein (TVP) into beef patties in different quantities (10–40%) and compare various characteristics of these innovative formulations with a regular beef patty as a control. Incorporation of 10–40% TVP resulted in significantly lower (p < 0.05) moisture and fat contents, while higher crude fiber contents were detected compared to beef as the control. In addition, cooked patties showed higher pH levels (p < 0.05), with color … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 47 publications
3
12
0
Order By: Relevance
“…For instance, Hidayat et al studied the effect of TVP on the quality of beef sausages and found that different degrees of TVP substitution improved the water-holding capacity and cooking yield of beef sausages while maintaining a good sensory acceptance up to 30% of TVP replacement [ 14 ]. Previously, the integration of TVP in beef patties modified the hardness, cohesiveness and toughness [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Hidayat et al studied the effect of TVP on the quality of beef sausages and found that different degrees of TVP substitution improved the water-holding capacity and cooking yield of beef sausages while maintaining a good sensory acceptance up to 30% of TVP replacement [ 14 ]. Previously, the integration of TVP in beef patties modified the hardness, cohesiveness and toughness [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Color indices were measured using a colorimeter (Color Flex EZ colorimeter, Hunter Associates Laboratory Inc., Reston, VA, USA). Before the measurement, a white plate (X = 80.59, Y = 85.72, Z = 91.97, Illuminant D65) was calibrated, and the sample was measured for brightness (L*), redness (a*), and yellowness (b*) using the Hunter scale [ 42 , 43 , 44 ].…”
Section: Methodsmentioning
confidence: 99%
“…Plant‐based products such as patties, burgers, and nuggets are a type of minced products which have distinct juiciness, chewiness, and firmness. Plant‐based texturized protein, vegetable lipid, and starch are the main ingredients used in the preparation of vegan minced products (Bakhsh, Lee, Lee, Hwang, & Joo, 2021; Kassama, Ngadi, & Raghavan, 2003). Bakhsh et al (2021) developed meatless patties using texturized isolate soy protein and commercial texturized vegetable protein with beef patty as control.…”
Section: Effect Of Foundational Elements and Processing On Texturementioning
confidence: 99%